The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/mi13050724
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Titanium and Copper-Coated Diamond/Copper Composites via Selective Laser Melting

Abstract: The poor wettability and weak interfacial bonding of diamond/copper composites are due to the incompatibility between diamond and copper which are inorganic nonmetallic and metallic material, respectively, which limit their further application in next-generation heat management materials. Coating copper and titanium on the diamond particle surface could effectively modify and improve the wettability of the diamond/copper interface via electroless plating and evaporation methods, respectively. Here, these dense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Considering that 1200 W is enough to get a continuous fusion when carbon is present, the reduction in the power laser reaches 40% to fuse copper in this experimental series. When it comes to the literature comparison, this reduction can be much more expressive since densities such as 100 kW/mm 2 are rarely obtained for Cu or Cu alloys [ 18 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that 1200 W is enough to get a continuous fusion when carbon is present, the reduction in the power laser reaches 40% to fuse copper in this experimental series. When it comes to the literature comparison, this reduction can be much more expressive since densities such as 100 kW/mm 2 are rarely obtained for Cu or Cu alloys [ 18 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main drawback when adding carbon to copper is its segregation generating pores and cracks in the final metal part [ 15 , 16 , 17 ]. Preliminary studies have shown reduced copper reflectance when using polymeric materials as an absorbing layer [ 13 , 18 ]. In addition, using a multilayer stack of several graded metal-carbon layers followed by an amorphous carbon film produces excellent selective solar absorbers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue article covers a wide range of forming materials, including steel [1,9] and other iron-based alloys [11], magnesium alloys [3], titanium alloys [6,12], copper alloys [7], aluminum alloys [13], composites (e.g., CF/PA12 [4], copper/titanium-coated diamond [14]) and, in particular, metallic multi-materials (e.g., NiTi/CuSn10 [2], copper/steel [7]) and 4D-printing materials (e.g., NiTi shape memory alloys [2,15], smart materials for soft interactive hydrogel [5]). et al [12] investigated types of Ti-6Al-4V (TC4) materials with different porosities fabricated via L-PBF using different printing parameters.…”
Section: Materials Of Laser Additive Manufacturing In This Special Issuementioning
confidence: 99%
“…Zhang et al [14] used the L-PBF technique to fabricate titanium-and copper-coated diamond/copper composites. The microstructure, roughness, interface bonding, thermal and mechanical performance were studied.…”
Section: Materials Of Laser Additive Manufacturing In This Special Issuementioning
confidence: 99%
“…AM technology emerged in the 1990s and has been under development for approximately three decades [8]. Unlike "subtractive manufacturing" (e.g., cutting, drilling, and milling) and "equal-material manufacturing" (e.g., welding, casting, and forging), AM is built on 3D models [9], relies on layer by layer printing-extrusion, sintering [10,11], melting, light curing, and jetting to form solids from metallic or non-metallic materials [12,13].…”
Section: Introductionmentioning
confidence: 99%